1992
DOI: 10.1182/blood.v80.6.1582.1582
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Spanish (delta beta)zero-thalassemia deletion by polymerase chain reaction

Abstract: delta beta-Thalassemia and hereditary persistence of fetal hemoglobin (HPFH) are inherited disorders characterized by the persistent synthesis of fetal hemoglobin (HbF) during adult life. The Spanish type of delta beta-thalassemia is a mild thalassemic condition due to a large deletion starting at the Alu I repeat between the A gamma and delta-globin genes immediately 3′ to the RIH probe and extending 11 and 17 kb downstream of the 3′ endpoints of HPFH 1 and HPFH 2, respectively. Using probes from the Spanish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Differences in the severity and pattern of the oxidative damage have been previously described between a-and P-thalassaemia due to different quantity of precipitated globin chains (20,21,22). To our knowledge, however, no studies on oxidative susceptibility to pro-oxidant stimuli have been previously reported on 6P-thalassaemia, a very frequent thalassaemia trait in some Mediterranean areas (23). Accordingly, the present study was undertaken in order to investigate the susceptibility to oxidative damage of RBCs in GP-thalassaemia trait in comparison to P-thalassaemia trait and IDA, where excessive production of free radicals in vivo is also warranted.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Differences in the severity and pattern of the oxidative damage have been previously described between a-and P-thalassaemia due to different quantity of precipitated globin chains (20,21,22). To our knowledge, however, no studies on oxidative susceptibility to pro-oxidant stimuli have been previously reported on 6P-thalassaemia, a very frequent thalassaemia trait in some Mediterranean areas (23). Accordingly, the present study was undertaken in order to investigate the susceptibility to oxidative damage of RBCs in GP-thalassaemia trait in comparison to P-thalassaemia trait and IDA, where excessive production of free radicals in vivo is also warranted.…”
Section: Introductionmentioning
confidence: 82%
“…Iron deficiency anaemia (IDA) was defined by a low MCV with serum iron < 40 pg/ dl and serum ferritin < 15 ng/ml in females and < 20 in males. P-thalassaemia trait was defined by the coexistence of microcytosis and increased HbA, and 6 s thalassaemia trait by the coexistence of microcytosis, increased HbF (5-15%) and a compatible PCR study for Spanish (6s)" thalassaemia (23). Concomitant ferropenic status was ruled out in all the patients with thalassaemia.…”
Section: Patientsmentioning
confidence: 99%
“…Recently, nearly 200 mutations have been characterized to produce ␤-thalassemia, which are mostly caused by point mutations [16]. There are 10 deletional forms of ␤-thalassemia that have been reported, ranging from 44-12622 bp [17][18][19]. In nine of them, the deletion regions have in common the 5Ј ␤-gene promoters, which exhibited an unusually high level of HbA 2 in the heterozygous state.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was obtained by salting out procedure . Genotyping was performed in two stages: (i) ARMS‐PCR to identify the six most frequent point mutations in Mexican population: Cd 39 C>T, IVS1:1 G>A, IVS1:110 G>A, ‐28 A>C, Cd initiation A>G and IVS1:5 G>A; and gap‐PCR for δβ‐thalassemia Spanish type as previously described; (ii) in those negative samples for the previous screening, DNA sequencing was performed to identify rare or new β‐thal alleles using Big dye terminator kit v3.1 and DNA sequencer ABI Prism 310 (Applied Biosystems). GenBank HBB sequence was used for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%